2018
DOI: 10.3892/ol.2018.7884
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic and clinicopathological value of melanoma-associated antigen D4 in patients with glioma

Abstract: The aim of the present study was to evaluate the clinical importance of melanoma-associated antigen D4 (MAGE-D4) expression in glioma, and to identify it as a valuable prognostic biomarker and therapeutic target. To achieve this, the expression of MAGE-D4 protein in 124 tumor tissues from patients with glioma was measured using reverse transcription-quantitative polymerase chain reaction (RT-qPCR) and immunohistochemistry (IHC), and the associations between MAGE-D4expression and clinicopathological factors wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 33 publications
0
12
0
Order By: Relevance
“…Further, this association was independent of IDH status and other clinically relevant variables. The association of MAGED4 overexpression with poor prognosis of glioma patients has been previously reported ( 46 ). In agreement to this, our analysis revealed that while MAGED1 , which is co-expressed with MAGED4 , was associated with poor prognosis in glioma, it did not emerge as an independent prognostic factor in multivariate analysis.…”
Section: Discussionmentioning
confidence: 69%
“…Further, this association was independent of IDH status and other clinically relevant variables. The association of MAGED4 overexpression with poor prognosis of glioma patients has been previously reported ( 46 ). In agreement to this, our analysis revealed that while MAGED1 , which is co-expressed with MAGED4 , was associated with poor prognosis in glioma, it did not emerge as an independent prognostic factor in multivariate analysis.…”
Section: Discussionmentioning
confidence: 69%
“…qRT-PCR was conducted as previously reported [ 9 ]. TRIzol reagent (Thermo Fisher Scientific, Waltham, MA, USA, #15596026) was used to extract the total RNA from glioma tissues and normal brain specimens.…”
Section: Methodsmentioning
confidence: 99%
“…IHC was conducted in accordance with previous research [ 9 ]. The tissues are formalin-fixed for 24 h at room temperature before being paraffin-embedded, and then cut into 4 µm-thick slices.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, relatively little is known about the localization and expression of type II MAGE proteins. Studies on type II MAGE-D4 have reported that its expression in normal tissues is restricted to the brain and ovary; however, it is overexpressed in several human malignancies, including lung, liver, oral, kidney, breast, and colorectal cancers, glioma (12)(13)(14)(15)(16)(17)(18), and ESCC, as previously reported by us (19). MAGE-D4 is a prominent tumor-associated antigen and has been shown to contribute to the proliferation, migration, and invasion of breast cancer and oral squamous cell carcinoma cells (14,16).…”
mentioning
confidence: 99%